Current perspectives on HIV-related pain and its management: insights from sub-Saharan Africa. (November 2011) - Kamerman, Peter R; Mitchell, Duncan
SUMMARY Sub-Saharan Africa is the region worst affected by the HIV epidemic and we estimate that at least 10 million HIV-positive individuals in sub-Saharan Africa live with significant pain related to their disease. Until recently there was a lack of studies specifically addressing pain related to HIV infection in sub-Saharan Africa, which limited our understanding of the scope of the problem. Here we describe the current nature of the epidemic of HIV-related pain in sub-Saharan Africa, including the systematic under-recognition and undertreatment of the pain.